PENGELOLAAN KONFLIK SOSIAL DAN KEARIFAN LOKAL MASYARAKAT ARKIPELAGO: PERAN ADMINISTRASI PUBLIK DAN KAJIAN SOSIOLOGI - Hildigardis M.I. Nahak; Aelsthri Ndandara (Jurnal Pluralis, 2023)
Social conflict is a phenomenon that often occurs in society. However, appropriate and effective management of social conflict is very important for the survival of a harmonious and peaceful society. In the context of archipelago, local community wisdom can be used as a tool to manage social conflict appropriately and effectively. This article discusses the role of public administration and sociological studies in managing social conflict by utilizing the local wisdom of the people in archipelago. Public administration is responsible for determining and implementing public policies, including policies for managing social conflict. Sociological studies provide an understanding of the social dynamics of society and the factors that trigger social conflict. According to Karl Marx, social conflict cannot be avoided, but with proper management, social conflict can be turned into an opportunity to strengthen social relations and improve the welfare of society.